The New Testament : a translation - Hart, David Bentley (Yale University Press, 2017)
"David Bentley Hart undertook this new translation of the New Testament etsi doctrina non daretur, "as if doctrine is not given." Reproducing the texts' often fragmentary formulations without augmentation or correction, he has produced an often pitilessly literal translation of the early Christians' sometimes raw, astonished, and halting prose, one that captures the texts' frequent impenetrability and unfinished quality while awakening readers to an uncanniness that often lies hidden beneath doctrinal layers. This rendering also challenges the idea that the New Testament affirms the kind of people we are. Hart reminds us that the first Christians were a company of extremists, radical in their rejection of the values and priorities of society not only at its most degenerate, but often at its most reasonable and decent. "To live as the New Testament language requires," he writes, "Christians would have to become strangers and sojourners on the earth, to have here no enduring city, to belong to a Kingdom truly not of this world. And we surely cannot do that, can we?""--Jacket flap.